2015
DOI: 10.12659/pjr.892529
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of Sacroiliitis According to ASAS Criteria: A Comparative Evaluation of Conventional Radiographs and MRI in Patients with a Clinical Suspicion of Spondyloarthropathy. Preliminary Results

Abstract: SummaryBackgroundThe objective of this study was a comparative evaluation of radiography and MRI in the diagnostics of sacroiliitis in patients with a clinical diagnosis of spondyloartropathy, according to the current ASAS criteria.Material/MethodsSacroiliac joints radiograms and MRI were conducted in 101 consecutive patients, aged 19–71 yrs (mean age: 40.6 yrs). The patients were referred by a senior rheumatologist, with symptoms of the chronic back pain. The sacroiliac joints were assessed on AP radiograms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…These results are of considerable significance in the light of further management and indicate that basing the diagnosis on radiographs according to the current ASAS classification criteria carries the risk of establishing an erroneous diagnosis of sacroiliitis. This is also confirmed by recent analyses [ 12 , 13 ]. Van der Berg et al [ 12 ] found that in patients with a recent-onset inflammatory back pain, both trained readers and local rheumatologists and radiologists agreed only moderately on the recognition of radiographic sacroiliitis.…”
Section: Discussionsupporting
confidence: 90%
“…These results are of considerable significance in the light of further management and indicate that basing the diagnosis on radiographs according to the current ASAS classification criteria carries the risk of establishing an erroneous diagnosis of sacroiliitis. This is also confirmed by recent analyses [ 12 , 13 ]. Van der Berg et al [ 12 ] found that in patients with a recent-onset inflammatory back pain, both trained readers and local rheumatologists and radiologists agreed only moderately on the recognition of radiographic sacroiliitis.…”
Section: Discussionsupporting
confidence: 90%
“…In the entire group of 130 children, active and chronic inflammatory lesions were detected in 41% of children whereas chronic changes were visualized only in patients with clinically suspected JSpA. Chronic inflammatory changes were detected on MRI more frequently than on radiographs (14.3% vs 6.7%), which is consistent with our studies conducted in adults ( 11 ) . Children with suspected JSpA, in whom active lesions were detected in MRI, also had considerably higher levels of C-reactive protein (p = 0.01) and significantly longer medical history (p = 0.01) compared to children without features of sacroiliitis in MRI: 63.2 ± 44.1 months vs 28.2 ± 29.7 months.…”
Section: Magnetic Resonance Imagingsupporting
confidence: 90%
“…These criteria have recently been updated with the inclusion of more radiologists on the ASAS consensus panel [19]. Recent studies have shown that administration of contrast is not recommended due to the cost, risks of side effects and prolonged scanning time [314202122]. …”
Section: Discussionmentioning
confidence: 99%